(Np(B.(NhINDEMITs - (Nt(B.(NlEWAQ(B.s; (No(B.(NlEONTXEWAs (NDRUGOJ AWTORs ((NmOSKWAs (NmUZYKAs, 1974)
(Nw KNIGE O KRUPNEJ[EM NEMECKOM KOMPOZITORE(B.(NTEORETIKE I PEDAGOGE hh WEKA OSWE]AETSQ TWOR^ESKIJ PUTX hINDEMITA I RASSMATRIWA@TSQ EGO GLAWNYE SO^INENIQ(B.s
Keywords: (NMONOGRAFIQs